Mediating Role of Perceived Fairness between Organizational Commitment, Organizational Trust and Work Engagement of Female Faculty Members of Public Sector Universities in Punjab, Pakistan - Quaisar Ijaz Khan; Mohsin Bashir; Maham Ali; Aqsa Javaid (Journal of Accounting and Finance in Emerging Economies, 2022)
Purpose: Ensuring the competitive advantages for female faculty members and to attain sustainable progress in rapidly transforming educational environment in the current era.